(3ELGRIs - (3GdegOj Hf eMeO Hf YHO Gddg Hf GdegdGs
(3ChdgG (B:s
(3hGdMeO ddg GdPi jSQ dfG GdSHjd Edi GdTQjYI GdSeMI hHYO , aEfg deG cGf ef GdJjSjQ Ydi gPg GdCeI EdJeS efi GdYdGeI TQa GdOjf SHW CejQ GdeDefjf Cf CLjR dg cJGH GdcGTa ddShd ai Md eYGfi GdcGad s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde eged GdfbW cKjQkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3eUOQ GbJfGA GdCUd (B:s
(3CeHQhRjGfG (B(8/244) s
Keywords: (3GdJGQjNs